Renal Cell Carcinoma With Inferior Vena Cava Tumor Thrombus in Two Patients With Previous Coronary Artery Bypass Graft: Strategy for Surgical Removal - Ciancio, Gaetano; Farag, Ahmed; Salerno, Tomas (Frontiers in Surgery, 2021)
Surgical management of renal cell carcinoma (RCC) with tumor thrombus (TT) extending into the inferior vena cava (IVC) and up to the hepatic veins and right atrium (RA) continues to be problematic and a challenging surgical operation. It becomes even more complicated when performing a re-sternotomy and cardiopulmonary bypass (CPB) in patients with previous coronary artery bypass grafting (CABG). Here, we report on 2 patients with previous CABG who presented with RCC and TT extending into the hepatic vein and above the diaphragm. These 2 patients underwent successful surgical resection and TT thrombectomy without the need of CBP. Recommendations are made for successfully accomplishing such surgical resections, including adequate prior preparation for the possible need to perform re-sternotomy and CPB with a coordinated team effort.